Baseline angiopoietin‐2 and FGF19 levels predict treatment response in patients receiving multikinase inhibitors for hepatocellular carcinoma. Issue 5 (11th April 2020) - Shigesawa, Taku; Suda, Goki; Kimura, Megumi; Shimazaki, Tomoe; Maehara, Osamu; Yamada, Ren; Kitagataya, Takashi; Suzuki, Kazuharu; Nakamura, Akihisa; Ohara, Masatsugu; Umemura, Machiko; Kawagishi, Naoki; et al.
Abstract: Background: Sorafenib and lenvatinib are first‐line systemic therapies for unresectable hepatocellular carcinoma (HCC). However, the criteria for their selection remain unclear. Methods: We identified patients with unresectable HCC who were treated with sorafenib or lenvatinib between August 2009 and January 2019 at the Hokkaido University Hospital. Patients who continued treatment for >2 months, underwent evaluation by computed tomography every 2–3 months, and had complete clinical data were included. Responders were patients with objective response (OR) for lenvatinib and patients with stable disease (SD) exceeding 6 months (long‐SD) or OR for sorafenib. The predictive factors for treatment response, including fibroblast growth factor (FGF)19 and 21, angiopoietin 2 (ANG2), hepatocyte growth factor, and vascular endothelial growth factor, were evaluated. Results: Overall, 27 and 29 patients treated with lenvatinib and sorafenib, respectively, were included. The responders for lenvatinib and sorafenib were 63% (17/27) and 38% (11/29), respectively. No significant predictive factors for treatment response were identified in patients treated with sorafenib. However, baseline serum FGF19 and ANG2 levels were significantly associated with treatment response to lenvatinib. All (9/9) patients with low baseline ANG2 and FGF19 levels who received lenvatinib achieved OR. Conversely, the OR was low (13%; 1/9) in patients with high baseline ANG2 and FGF19 levels. Responder rate was 40% (2/5) in patients with high baseline ANG2 and FGF19 levels who received sorafenib. Conclusion: This study is, to our knowledge, the first to demonstrate that baseline ANG2 and FGF19 levels may aid in selecting optimal systemic therapy for patients with unresectable HCC. Abstract : The combination of baseline serum ANG2 and FGF19 levels may predict treatment response to lenvatinib in patients with unresectable HCC. An OR was achieved in all patients with low baseline levels of ANG2 and FGF19 treated with lenvatinib (100%, 9/9). Conversely, those with high baseline levels of these markers demonstrated a low OR rate (13%; 1/9). However, in patients with high baseline ANG2 and FGF19 levels, the response to sorafenib was not low (40% 2/5). These findings show, for the first time, that baseline biomarker levels may determine suitability for systemic therapy in patients with unresectable HCC.